The Role of European Union in Refugee Crisis on Belarusian Border – European Union in 2021 - 2022 - Christiani, Safira; Elyta, Elyta; Wicaksono, Azzomarayosra (International Journal of Multidisciplinary Approach Research and Science, 2024)
This article aims to analyze the role of the European Union in handling the refugee crisis at the Belarusian-European Union border in 2021-2022. The refugee crisis at the Belarusian-European Union border poses significant challenges for the European Union in various aspects, such as politics, security, and humanity. This research uses a qualitative approach and is then analyzed to explain the evaluation of the European Union's policies, responses, and strategies in responding to this crisis. Through an in-depth study of the policies and actions taken by the European Union, this article outlines the European Union's response to the refugee crisis on the Belarus – European Union border. This includes diplomatic efforts, humanitarian assistance, and security strategies implemented by the European Union to address problems arising from the crisis. In addition, this article also analyzes the challenges faced by the European Union in dealing with this refugee crisis, including coordination between member countries and internal political consequences. This research found that the role of the European Union in the refugee crisis on the Belarus-European Union border is in the form of providing financial assistance to refugees trapped in the border area. The European Union has also facilitated the Schengen forum, which will be held in 2022. The European Union has also closed its border areas due to the interests of national member countries with direct borders, such as Poland, Latvia, and Lithuania. The European Union also imposed sanctions on Belarus because it was deemed responsible for the crisis that occurred.